2013
DOI: 10.1111/prd.12004
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation of modern oral implants with emphasis on crestal bone level and relevance to peri‐implant health

Abstract: Implant stability and maintenance of stable crestal bone level are prerequisites for the successful long-term function of oral implants, and continuous crestal bone loss constitutes a threat to the longevity of implant-supported prosthetic constructions. The prevalence/incidence and reasons for crestal bone loss are under debate. Some authors regard infection (i.e. peri-implantitis) as the cause for virtually all bone loss, while others see crestal bone loss as an unavoidable phenomenon following surgery and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 87 publications
4
92
1
3
Order By: Relevance
“…De Bruyn, Vandeweghe, Ruyffelaert, Cosyn and Sennerby (2013) reviewed radiographic assessment of modern implants and suggested that this mean bone loss assessment in patients with multiple implants yields very limited information on the condition of individual implants. However, it may be valid to benchmark implant systems.…”
Section: Introductionmentioning
confidence: 99%
“…De Bruyn, Vandeweghe, Ruyffelaert, Cosyn and Sennerby (2013) reviewed radiographic assessment of modern implants and suggested that this mean bone loss assessment in patients with multiple implants yields very limited information on the condition of individual implants. However, it may be valid to benchmark implant systems.…”
Section: Introductionmentioning
confidence: 99%
“…The main disagreement was on when the initial x-ray should be taken: when the implant is placed, when the restoration is placed or after bone remodeling. This workshop found greater scientific evidence, as well as agreement among authors, supporting initial radiographic examination, after postrestoration bone remodeling (11,13,14) .…”
Section: Fig 6 Probing Depthmentioning
confidence: 68%
“…La discrepancia fundamental se centra en la oportunidad de obtener la radiografía inicial: al momento de la colocación del implante, cuando se instala la rehabilitación o posterior al remodelado óseo. Este taller encontró mayor evidencia científica, así como coincidencia entre los autores, que sugieren el control radiográfico inicial, luego del remodelado óseo post rehabilitación (11,13,14) .…”
Section: Fig6 Profundidad De Sondajeunclassified
“…Radiographical methods remains the most widely used in the different modification to evaluate peri-implant bone level changes [13,14,16]. In the course of this study, it was found that the level of bone resorption after one year of implant functioning could be established according to the data obtained from digital sagittal cross section of CBCT results, because this method by its methodology of evaluation does not different from those one with the use of periapical X-ray images.…”
Section: Discussionmentioning
confidence: 83%
“…The most widely used method is periapical radiography, but such method still is operator sensitive and not enough reliable [9,12,13]. On the other hand, such method allows only registering bone changes from the medial and distal sides of dental implant, and does not include the possibility to find out the exact volume of circular bone loss around intraosseous titanium element.…”
Section: Introductionmentioning
confidence: 99%